Young and Recognized in Service Interaction? Re-positioning Youth and Adulthood with Performance Tactics and Strategic Laughter. (February 2018) - Kylkilahti, Eliisa; Autio, Minna
Young consumers hold an iconic position in post-industrial cultures. In spite of youth idealization in consumer culture, we know little of how youth is situated in everyday interactions in service culture. In our study, we focus on age-related power structures in service encounters. We argue that customer service interaction is built on the norm of an adult order; that is, to achieve an appreciated position as a customer, young people are required to act like 'middle-aged' consumers. To gain recognition, young consumers use resistance tactics: They create co-performing teams together with adults and modify their own performance towards adulthood by masking signs of youth. The findings suggest that young people may also resist the dominant adult order; laughter and smiling express a strategy that re-positions adults into a less powerful position in the service environment. The study shows that young and adult categories in service interaction are constantly under re-negotiation.